KESENIAN DAN TEKNOLOGI DI ERA DISRUPSI (Studi Terhadap Akun Instagram Madihin @gazali_rumi) - Rahmi Hartati; Najla Amaly (UIN Antasari Banjarmasin, 2020)
Instagram is one of the most popular social media in the new media age community, including the people of Indonesia. Based on survey data released by the Indonesian Internet Service Providers Association (APJII) in 2016 there were 19.9 million Instagram accounts registered. Instagram not only uses the media to post pictures of daily activities, but already uses promotional facilities and to preserve the culture. Madihin is a culture originating from South Kalimantan. The @gazali_rumi account is an Instagram account that has Madihin art posts. Social media can be the latest innovation in preserving this traditional art, while social media has become a characteristic of modern society today.